Consumer Demand with Unobservable Product Attributes - Part I: Theory - John K. Dagsvik (Statistics Norway, Research Department, 1996)
This paper develops a new framework for empirical modelling of consumer demand with particular reference to products that are differentiated with respect to quality and location attributes. The point of departure is a flexible representation of the distribution of product attributes and consumer tastes. From this representation and additional behavioral assumptions we derive a structural model for the distribution of the chosen product attributes and the associated quantities. Furthermore, an explicit relationship between the distribution of prices and unit values is obtained.
Keywords: C25; C43; D11; 330; Price distribution; differentiated products; quality attributes; hedonic price indexes.